Self-Confidence, 10th Edition - McGee, Paul (Capstone, 2020)
The special Tenth Anniversary Edition of the classic, bestselling guide to increasing self-confidence and boosting personal and professional success Confidence is profoundly important to virtually every aspect of our lives - it's the main ingredient for handling anything thrown at us. Whether in our school or business careers, personal relationships or the way in which we present ourselves to the world, confidence is often the deciding factor between success or failure. But how does one increase self-confidence? Sunday Times best sellingAuthor Paul McGee has helped thousands of people answer this very question with his bestselling book Self-Confidence . Blending Paul's humour and wit with expert insights and practical advice, this beloved resource remains the essential guide to increasing self-confidence and boosting success. Paul shows you how increasing your confidence by even a small amount can lead to dramatic positive changes in your life. Celebrating its tenth year in publication, this new Anniversary Edition has been extensively updated to addresses current "hot topics" and trends for improving confidence and driving personal and professional success. Paul offers new guidance on strengthening resilience, promoting well-being, enhancing mental health and much more. Along the way, Paul shares honest and very personal stories from his own life to highlight important lessons and reinforce your confidence-building process. This must-have guide will help you: Understand how making small changes will yield enormous results Manage self-doubt and overcome anxiety Discover who or what crushed your confidence and meet them head-on Refuse to let setbacks sap your confidence by turning them into motivation to forge ahead Step away from your comfort zone and achieve what you always wanted, but lacked the confidence to pursue The special edition of Self-Confidence provides everything you need to start on the path to increased confidence, resilience and success. You will be astonished by what you can accomplish when you have the confidence to try.